HACCP : a practical approach - Mortimore, Sara (Springer US, 2013)
HACCP: A Practical Approach, 3rd edition has been updated to include the current best practice and new developments in HACCP application since the last edition was published in 1998. This book is intended to be a compendium of up-to-date thinking and best practice approaches to the development, implementation, and maintenance of HACCP programs for food safety risk reduction. Introductory chapters set the scene and update the reader on  HACCP developments over the last 15 years. The preliminary stages of HACCP, including preparation, planning and system design, are covered first, followed by a consideration of food safety hazards and their control. Prerequisite program coverage has been significantly expanded in this new edition, reflecting its development as a key support system for HACCP. The HACCP plan development, verification and maintenance chapters have also been substantially updated to reflect current practice and a new chapter on application within the food supply chain has been added. Appendices provide a new set of case studies of practical HACCP application plus two new case studies looking at lessons learned through food safety incident investigation. Pathogen profiles have also been updated by experts to provide an up-to-date summary of pathogen growth and survival characteristics that will be useful to HACCP teams. The book is written both for those who are developing HACCP systems for the first time and for those who need to update, refresh and strengthen their existing systems. New materials and new tools to assist the HACCP team have been provided and the book discusses the current situation on issues that are still undergoing international debate, such as operational prerequisite programs. Sara Mortimore is the Vice President of Product Safety, Quality Assurance, and Regulatory Affairs at Land O'Lakes, Inc., USA. Carol Wallace is Principal Lecturer, Food Safety Management and Co-Director of the International Institute of Nutritional Sciences and Applied Food Safety Studies at the University of Central Lancashire, UK.